Yeast as a Model to Unravel Mechanisms Behind FUS Toxicity in Amyotrophic Lateral Sclerosis - Lindström, Michelle; Liu, Beidong (Frontiers in Molecular Neuroscience, 2018)
FUS (fused in sarcoma) is a multifunctional DNA/RNA-binding protein predominantly localized in the cell nucleus. However, FUS has been shown to accumulate and form aggregates in the cytoplasm when mislocalized there due to mutations. These FUS protein aggregates are known as pathological hallmarks in a subset of amyotrophic lateral sclerosis (ALS) and frontotemporal lobar degeneration (FTLD) cases. In this review, we discussed recent research developments on elucidating the molecular mechanisms behind FUS protein aggregation and toxicity. We mainly focus on studies using the budding yeast (Saccharomyces cerevisiae) as a model system, especially on results acquired from yeast genome-wide screens addressing FUS aggregation and toxicity. Human homologs of the FUS toxicity suppressors, identified from these studies, indicate a strong relevance and correlation to a human disease model. By using yeast as a FUS cytotoxicity model these studies provided valuable clues on potential novel targets for therapeutic intervention in ALS.